Horse trading : food sourcing in the twenty-first century - Walker, Russell, 1972-; Wilson, Joanna (Urbanist and food activist) (London : SAGE Publications Ltd, 2017)
In January 2013, Irish authorities were the first to uncover the years first food sourcing scandal: horsemeat sold as beef on supermarket shelves. It was not long before regulators and retailers realized the problem was truly a continental one. The incident involved French exporters, Luxembourger production facilities, Cypriot and Dutch meat traders, British and Swedish retailers, and Romanian horsemeat. Food service providers and retailers were forced to test beef products to ensure they were horse-free, pulling products that contained traces of equine meat. British supermarkets alone disposed of an estimated 10 million beef burgers in the wake of the scandal.This case is an example of the challenges of managing the complex global supply chains that make up the modern food industry. In this class discussion, students will use concepts from management, economics, and public policy to assess the damage of this event and to analyze strategies for preventing similar incidents in the future.
Originally published in Walker, R. (2016). Horse trading: Food sourcing in the twenty-first century. 5-216-250. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Food industry and trade -- Quality control; Food industry and trade -- Management; Meat industry and trade; Food -- Safety measures; Horsemeat